2009
DOI: 10.3233/isb-2009-0403
|View full text |Cite
|
Sign up to set email alerts
|

PlasmoID: A P. falciparum Information Discovery Tool

Abstract: Plasmodium falciparum is the parasite responsible for more than 90% of deaths that occur due to malaria. Organization and mining of 'omic' (genomic, proteomic, transcriptomic, interactomic) data can improve our understanding of P. falciparum biology and help in the fight against malaria. PlasmoID (Plasmodium Information Discovery) is a tool developed for the dynamic exploration of the parasite's 'omic' landscape. Diverse computational and curated P. falciparum protein-protein interaction datasets, as well as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Therefore, the analysis requires an understanding of the protein networks and their importance in the biological system. Understanding the topological metrics using an in silico approach has further paved the way for exploring proteins in detail with the help of software such as PSIMAP [157] and PlasmoID [158]. A similar protein interaction and network studies have been reported for L. major using an in silico approach with iPfam, PEIMAP and PSIMAP [159].…”
Section: Modulation Of the Leishmania Proteome Profilementioning
confidence: 96%
“…Therefore, the analysis requires an understanding of the protein networks and their importance in the biological system. Understanding the topological metrics using an in silico approach has further paved the way for exploring proteins in detail with the help of software such as PSIMAP [157] and PlasmoID [158]. A similar protein interaction and network studies have been reported for L. major using an in silico approach with iPfam, PEIMAP and PSIMAP [159].…”
Section: Modulation Of the Leishmania Proteome Profilementioning
confidence: 96%
“…These studies have also expanded to organisms of medical importance, such as the protozoan parasite Plasmodium falciparum [ 20 ], in the interest of discovering new drug and vaccine targets. This data is available through the system PlasmoID [ 21 ]. Topological analysis has also been useful in detecting important proteins, even when the protein network has been predicted using an orthology-based method, as in the case of the human interactome[ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid sequences of conserved Plasmodium proteins of unknown function were also analyzed in OrthoMCL-DB [47] . Clusters and protein interaction networks were built in Cytoscape 2.5.1 [48] using the PlasmoID database [49] , which integrates data from different experimental and computational resources, including LaCount DJ [23] and PlasmoMAP [24] datasets. The GO Term Finder tool [50] was used at the web interface http://go.princeton.edu/cgi-bin/GOTermFinder to identify ontology terms significantly enriched among the putative albitiazolium targets.…”
Section: Methodsmentioning
confidence: 99%